Walka o uznanie a tożsamość zawodowych aktorek - Jawor-Przybyszewska, Dorota (Studia Edukacyjne, 2016)
The text presented here is a fragment of a larger study on a private and social life of a group of women, actresses. It concerns attempts to create and show their own identity according to their fight for recognition (self-trust, self-estimation in the society, in the family environment, in public space as well as in their own opinions). The strategy of this study was qualitative research, based on a grounded theory methodology. The study was performed on 27 actresses, divided into three age groups. All the studied subjects had a very good economic status and all were successful professionals. The article presents an analysis carried out on the basis of a free flowing but planned interview. The struggle for recognition is treated as a way of restoring a constantly threatened personality and describes the contemporary woman, her situation and her actions. This research shows the problem that professional women come across, namely the women are successful actresses but at the same time wish to be fulfilled in their family lives. Amongst the 18 actresses over the age of 40, 14 talked about taking anti-depressants or about alcohol dependence. Further detailed analysis of the empirical material can help to find the source of the processes, which are a sign of a lack of recognition and which pose a threat to the integrity of the human identity and destroy the social bond which constitutes identity.